2009
DOI: 10.1074/jbc.m109.009365
|View full text |Cite
|
Sign up to set email alerts
|

Relevance of Fatty Acid Covalently Bound to Escherichia coli α-Hemolysin and Membrane Microdomains in the Oligomerization Process

Abstract: ␣-Hemolysin (HlyA) is an exotoxin secreted by some pathogenic strains of Escherichia coli that causes lysis of several mammalian cells, including erythrocytes of different species. HlyA is synthesized as a protoxin, pro-HlyA, which is activated by acylation at two internal lysines Lys-563 and Lys-689. It has been proposed that pore formation is the mechanism of cytolytic activity for this toxin, as shown in experiments with whole cells, planar lipid membranes, and liposomes, but these experiments have yielded … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
66
0
11

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(78 citation statements)
references
References 46 publications
1
66
0
11
Order By: Relevance
“…This circumstance obtains for HlyA, where an oligomer was found at lytic concentrations in sheep-erythrocyte ghosts. In contrast, no oligomeric structure was found for proHlyA (Herlax et al, 2009). …”
Section: Promotion Of Protein Oligomerizationmentioning
confidence: 74%
See 4 more Smart Citations
“…This circumstance obtains for HlyA, where an oligomer was found at lytic concentrations in sheep-erythrocyte ghosts. In contrast, no oligomeric structure was found for proHlyA (Herlax et al, 2009). …”
Section: Promotion Of Protein Oligomerizationmentioning
confidence: 74%
“…To carry out this study, two populations of HlyA K344C mutant proteins, one labelled with donor (Alexa-488) and the other with acceptor fluorophores (Alexa-546), were bound to sheep-erythrocyte ghosts. Our report showed that an oligomer was involved in the hemolytic mechanism of HlyA (Herlax et al, 2009). FRET can be used to study the distribution of molecules in membranes because the average spacing between molecules of interest will depend primarily on their lateral arrangement.…”
Section: Promotion Of Protein Oligomerizationmentioning
confidence: 99%
See 3 more Smart Citations